Unnatural acts : a Stone Barrington novel - Woods, Stuart (Woods, Stuart. Stone Barrington novel., 2012)
When a hedge fund billionaire hires Stone Barrington to talk some sense into his wayward son, it seems like an easy enough job; no one knows the hidden sins and temptations of the ultra-wealthy better than Stone. But as Stone and his erstwhile protege, Herbie Fisher, probe deeper into the case--and an old one comes back to haunt him---he realizes that even he may have underestimated just how far some people will go to cover up their crimes...and plan new ones.